2017
DOI: 10.1101/106385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The house spider genome reveals an ancient whole-genome duplication during arachnid evolution

Abstract: Background: The duplication of genes can occur through various mechanisms and is thought to make a major contribution to the evolutionary diversification of organisms. There is increasing evidence for a large-scale duplication of genes in some chelicerate lineages including two rounds of whole genome duplication (WGD) in horseshoe crabs. To investigate this further, we sequenced and analyzed the genome of the common house spider Parasteatoda tepidariorum.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 130 publications
(155 reference statements)
0
14
0
Order By: Relevance
“…This is an indication that recent gene duplication and loss is very low in this group, and that our results are not compromised by the deep arachnid whole-genome duplication (Schwager et al 2017). It also indicates that the individuals whose DNA was pooled for each species were quite similar (the assembler interpreted any differences at the level of allelic differences).…”
Section: Methodsmentioning
confidence: 48%
“…This is an indication that recent gene duplication and loss is very low in this group, and that our results are not compromised by the deep arachnid whole-genome duplication (Schwager et al 2017). It also indicates that the individuals whose DNA was pooled for each species were quite similar (the assembler interpreted any differences at the level of allelic differences).…”
Section: Methodsmentioning
confidence: 48%
“…Moreover, the distributions of these two hox clusters in T. tridentatus are very similar with its closely species, such as spider ( Parasteatoda tepidariorum ) and scorpion ( Centruroides sculpturatus ). These results indicated that hox clusters are very conservative in evolution and thus we have assembled a highly integrated genome (Figure c; Schwager et al., ). The results could further contribute to the study of specific body plan in T. tridentatus .…”
Section: Resultsmentioning
confidence: 83%
“…Whereas tsh represses expression of the gnathal Hox genes labial ( lab ) and Sex combs reduced ( Scr ) in the trunk D. melanogaster , tio/tsh expression of both arachnids encompasses the expression domains of their lab , Deformed ( Dfd ), and Scr orthologs (Röder et al, ; Khadjeh et al, ; Sharma et al, ). In addition, whereas trunk Hox genes like Antp and Ubx maintain tsh expression in the posterior compartment of specific D. melanogaster trunk segments, homologs of neither of these genes are expressed in the prosoma of arachnids during stages corresponding to leg fate specification (Khadjeh et al, ; Schwager et al, ; Sharma et al, ; Sharma, Schwager, Extavour, & Wheeler, ). Furthermore, the limited data available on Hox gene function in arachnids (e.g., lab‐ 1, Dfd‐1 , Antp‐1 ), in addition to expression patterns of centipede posterior Hox genes in the posterior trunk (the region correspond to the appendage‐free insect abdomen), have shown that orthology of Hox genes does not correspond to homology of function between insects, centipedes, and arachnids (Hughes & Kaufman, ; Khadjeh et al, ; Pechmann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A single 2906‐bp fragment of P. tepidariorum tio/tsh ortholog was identified from the developmental transcriptome and genome of this species (Posnien et al, ; Schwager et al, ), using the Drosophila melanogaster tio and tsh sequences as queries. Gene specific primers were designed for a 794‐bp fragment of Ptep‐tio/tsh .…”
Section: Methodsmentioning
confidence: 99%